Development of talent training mode for higher education institutions-enterprise cooperation in Tianjin City - Wen, Chengyu; Chutimant, Poramatdha (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of the study is to explore the level and composition of the development of talent training for higher education institutions-enterprise cooperation of 44 Chinese colleges and universities in Tianjin city. A mixed-methods approach was adopted for this research. After conducting an extensive literature review, a quantitative research methodology was employed using a 5-level Likert-scale questionnaire. The survey was distributed to 484 respondents, selected through stratified random sampling. An Exploratory Factor Analysis (EFA) was carried out to analyze the data, with a group of 9 experts providing an importance assessment of the identified factors. The EFA revealed that the factors influencing the development of the talent training mode can be grouped into eight key categories. These categories, ranked by priority, are: Career Planning Cognition (Mean=0.02, S.D=0.98), Employment Intention (Mean=0.01, S.D=0.92), Personal Ability (Mean=0.02, S.D=0.89), Employment Guidance (Mean=-0.01, S.D=0.85), Internship Practice (Mean=-0.02, S.D=0.80), Employment Mentality (Mean=0.03, S.D=0.78), New Technology Employment Market (Mean=0.05, S.D=0.76), Employment Resources (Mean=-0.01, S.D=0.70). Each factor was assessed for its mean score and standard deviation, indicating varying degrees of importance and variation in responses. The study concludes that effective talent training in colleges and universities depends on a combination of factors, with Career Planning Cognition and Employment Intention emerging as the most critical. The findings emphasize the need for a holistic approach that integrates both academic and industry perspectives to enhance the employability of graduates. The results of this research provide valuable insights for colleges and universities, enterprises, and policymakers in optimizing talent training modes. By focusing on the identified key factors, institutions can improve career guidance, enhance internship opportunities, and better align educational programs with the evolving demands of the employment market, particularly in the context of technological advancements.